How Accurately do English for Academic Purposes Students use Academic Word List Words? - Kim McDonough (BC TEAL Journal, 2018)
Previous corpus research on English for academic purposes (EAP) writing has analyzed how often additional language (L2) writers use words from the Academic Word List (AWL) (Coxhead, 2000), but few studies to date have explored how accurately those words are used. Therefore, the current study investigated how accurately and appropriately EAP writers (N = 409) use AWL words in their argumentative essays. The 230,694-word corpus was analyzed to identify AWL word families that occurred with at least 20 tokens. All tokens were then coded as being accurately used, or as containing a morphosyntactic or collocational error (or both). The findings showed that the EAP students’ overall accuracy rate was high (67%) and that collocational errors occurred more frequently than grammatical errors. Pedagogical implications for EAP programs are discussed.